Meningkatkan Motivasi Belajar Siswa Melalui Penerapan Model Pengajaran Langsung Dengan Metode Demonstrasi - Normaliani Normaliani; M. Arifuddin Jamal; Suyidno Suyidno (Universitas Lambung Mangkurat, 2013)
Lack of student motivation in science subjects especially physics knew about 30.3% of students was not excited each subject physics, 48% of students have difficulties in learning physics, and about 24% of students find it difficult to attend classes every physics. The research aims to improve students' motivation class X KORPRI Banjarmasin on the subject of straight motion through the application of the direct teaching method demonstration. The specific objective of the research is to describe the ability of teachers to manage student learning outcomes and student responses. Research subjects 21 students of class X school KORPRI Banjarmasin academic year 2012/2013. Techniques of data collection using questionnaires, observation sheets, and tests. The results of research documentation stating (1) the ability of the teacher in direct instruction on each cycle are very good (2) increase student motivation through attention aspect, relevance, confidence, and satisfaction. In the first cycle, there are aspects that are good enough attention. In the second cycle, all aspects categorized as good while the third cycle all aspects very well. (3) in the classical style in the first cycle increased by 63% (not finished), the second cycle of 85% (complete), and the third cycle of 100% (complete). (4) the response of interest in the model with the method of direct teaching demonstrations on aspects of both ARCS category on aspect attention 78%, 74.4% relevance, confidence68%, and satisfaction 72,8% class X SMAKORPRI Banjarmasin on material teaching straight motion.